Telaah Kritis Aksiologi Sains Modern Persepektif Naquid Al-Attas dan Implementasinya Dalam Komunikasi Ilmiah - Desta Amelia Dewi; Indah Robiatil Adawiyah; Lutfiatul Hasanah; Sitti Wahyuni; Alfina Wildatul Fitriyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The modern scientific revolution, which Thomas Kuhn said was caused by a shift in the scientific paradigm, brought major changes totechnological developments, especially in the 20th century. Apart from modern science bringing many benefits to humans, it turns out toobrings extraordinary side effects, including continuous natural damage and humanitarian disaster, as also statedby Naquib Al-Attas. The scientific challenges brought by Western culture have resulted in the development of modern science which is full of Western view of reality and truth. One of the elements of Western civilization is tragedy that shows the search the truth and nature and purpose of life are endless, so he is always in search, but never achieves what he wantssearching for. This perspective also influenced the development of modern science. This article attempts to explicitly highlight the effects aside from modern science, as well as Naquib Al-Attas's view of modern science from its axiological side. Method usedis an in-depth literature review. From this article it can be stated with certainty that the treasures of Islamic scholarship have providedfoundation for the development of knowledge, especially science. This is proven in the history of Islamic civilization, how the ulama and Muslim scientists provide clear signs in the development of science. One important aspect that needs to be considered is maqashid syari'ah for the development of science. The way of looking at nature as an object and humans as a subject must be referred to to the Islamic perspective of viewing reality and truth. Besides that, the paradigm of scientific development and progress Modernism must refer to a paradigm based on an Islamic worldview which emphasizes that development and progress are necessary focused on one constant thing, namely the purpose and meaning of human life as caliph on Earth. This frame of mind can become a reference for the scientific community to be able to truly play the role of caliph on Earth, so that they can prevent further natural damage and human disasters.